2022
DOI: 10.3390/ijms232415489
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Fatty Liver Disease (NAFLD) Pathogenesis and Natural Products for Prevention and Treatment

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most prevalent chronic liver disease, affecting approximately one-quarter of the global population, and has become a world public health issue. NAFLD is a clinicopathological syndrome characterized by hepatic steatosis, excluding ethanol and other definite liver damage factors. Recent studies have shown that the development of NAFLD is associated with lipid accumulation, oxidative stress, endoplasmic reticulum stress, and lipotoxicity. A range of natural product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(86 citation statements)
references
References 124 publications
1
78
0
7
Order By: Relevance
“…HepG2 cells are widely used in in vitro NAFLD models because they have the characteristics of hepatocytes that accumulates intracellular lipids by FFA treatments such as oleic acid and/or palmitic acid [ 9 , 34 , 35 ]. Many studies have reported that the exposure of HepG2 cells to 0.5–1 mM of FFA for 24 h results in significant lipid accumulation [ 16 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HepG2 cells are widely used in in vitro NAFLD models because they have the characteristics of hepatocytes that accumulates intracellular lipids by FFA treatments such as oleic acid and/or palmitic acid [ 9 , 34 , 35 ]. Many studies have reported that the exposure of HepG2 cells to 0.5–1 mM of FFA for 24 h results in significant lipid accumulation [ 16 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, polyphenol compounds have been shown to inhibit lipogenic enzyme activity and control new lipid synthesis [ 7 , 8 ]. Given that inflammation and oxidative stress are primary risk factors involved in the development of NAFLD [ 9 ], recent studies have reported that consuming a polyphenol-rich diet could help prevent and treat NAFLD [ 10 ]. Accordingly, considerable efforts have been made to assess the effectiveness of polyphenols on insulin resistance and metabolic pathologies in NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…NASH is considered the progressive form of NAFLD and is characterized by liver steatosis, inflammation, hepatocellular injury and different degrees of fibrosis ( Schuster et al, 2018 ). Accumulating studies demonstrated that a pivotal issue relates to the identification of those factors that trigger inflammation, thus fuelling the transition from NAFLD to NASH ( Guo et al, 2022 ; An et al, 2023 ). These triggers of inflammtion in liver might be associated with their origins outside the liver as well as inside the organ, both of which accelerate to NASH development ( Han et al, 2022 ).…”
Section: Extrahepatic Factors In Nashmentioning
confidence: 99%
“…10,12 Because of their low side effects and high safety, natural products have recently become a research hotspot for human health-related issues. 13 Lycium barbarum , a traditional Chinese edible and medicinal plant, 14 is also known as Goji berry and Chinese wolfberry. 15 According to related studies, the main active components of the plant are polyphenols, pigments, polysaccharides, flavonoids, amino acids, alkaloids, vitamins, and trace minerals.…”
Section: Introductionmentioning
confidence: 99%